INFLUENCE OF SKIM MILK CONCENTRATION ON THE PROXIMATE, CHEMICAL, AND MICROBIOLOGICAL PROPERTIES OF POWDERED BUFFALO COLOSTRUM KEFIR - Heni Rizqiati; Edi Prayitno; Meri Andani (Fakultas Teknologi Pertanian Universitas Brawijaya, 2025)
Adding fillers to kefir improves the stability and physical properties of kefir, so as to produce good kefir powder from the drying process. This study was conducted to determine the effect of skim milk addition as filler with different concentrations (0%, 2.5%, 5%, 7.5%, 10%) on the proximate, chemical, and microbiological properties of buffalo colostrum kefir powder using the spray dryer method. Increasing skim milk’s concentration had a significant effect (p<0.05) on proximate, chemical, and microbiological properties, except for total dissolved solids in the product. Increasing the concentration of skim milk enhanced solubility, total dissolved solids, yield, pH, total lactic acid bacteria, yeast, and microbial counts, while reducing moisture content, protein content, fat content, and titratable acidity. The addition of skim milk with the highest concentration produced a yield of 27.51%, caused by the drying factor with a spray dryer. It produced yeast of 7.43 log CFU/g and lactic acid bacteria of 5.17 log CFU/g, with lactic acid bacteria levels lower than the standard due to suboptimal drying and encapsulation processes. The best treatment in this study was the addition of 10% (w/v) skim milk.